The PENGARUH BI RATE DAN JUMLAH UANG BEREDAR TERHADAP INFLASI DI INDONESIA TAHUN 2010-2024 - Rio Firas Doras Talo Cipto; Ladi Wajuba Perdini Fisabilillah (Jurnal Ekonomika : INDEPENDEN, 2026)
This quantitative study analyzes the effect of the BI Rate and Money Supply (JUB) on Inflation in Indonesia from 2010-2024 using monthly data and multiple linear regression (OLS). The partial test results show The BI Rate has a positive and significant effect on inflation, which deviates from theory and is likely influenced by policy time lag. JUB has a negative and significant effect on inflation, contradicting the quantity theory of money, indicated by liquidity absorption in the non-real sector or saving behavior. Simultaneously, the BI Rate and JUB significantly influence inflation, with the model explaining 49.89% of the variation. This study concludes that the monetary transmission mechanism in Indonesia does not always align with conventional theory and requires policies that consider time lag and structural conditions.